2022
DOI: 10.21203/rs.3.rs-2304556/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microstructural and functional plasticity following repeated brain stimulation during cognitive training in non-demented older adults

Abstract: The combination of repeated behavioral training with transcranial direct current stimulation (tDCS) holds promise to exert benefial effects on brain function beyond the trained task. However, little is known about the underlying mechanisms. This was adressed by multimodal magnetic resonance imaging (MRI) before and after a three-week executive function training with prefrontal excitatory tDCS in 48 older adults. Results demonstrate that training combined with active tDCS enhanced prefrontal white matter micros… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 65 publications
0
5
1
Order By: Relevance
“…Supporting our positive behavioral effects, we observed FC alterations in the frontoparietal network in the anodal group compared to the sham group. While our previous study with healthy older adults (29) reported post-MR data immediately after the three-week intervention, here, we showed FC effects lasting seven months after the intervention. Speci cally, FC of the stimulation target in the left-hemispheric middle frontal gyrus with the angular gyrus and the superior/middle frontal gyrus in the right hemisphere, cortical areas known to be part of the frontoparietal executive control network, was increased (27).…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…Supporting our positive behavioral effects, we observed FC alterations in the frontoparietal network in the anodal group compared to the sham group. While our previous study with healthy older adults (29) reported post-MR data immediately after the three-week intervention, here, we showed FC effects lasting seven months after the intervention. Speci cally, FC of the stimulation target in the left-hemispheric middle frontal gyrus with the angular gyrus and the superior/middle frontal gyrus in the right hemisphere, cortical areas known to be part of the frontoparietal executive control network, was increased (27).…”
Section: Discussioncontrasting
confidence: 68%
“…Resting-state fMRI data were analyzed using the CONN toolbox (www.nitrc.org/projects/conn) (39) and SPM (40), with all settings chosen as in our previous study with healthy older adults (29). Preprocessing: Functional and anatomical data were preprocessed using a exible preprocessing pipeline (41) including realignment with correction of susceptibility distortion interactions, slice timing correction, outlier detection, direct segmentation and MNI-space normalization, and smoothing.…”
Section: Functional Connectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…These transfer effects are also theorised to be tied to early phases of structural plasticity within overlapping networks 19 . The 'neural overlap hypothesis' has been supported by evidence from concurrent tDCS during cognitive training resulting in microstructural brain alterations alongside near-transfer behavioural effects 34,49 . Since the motor learning paradigm used in this study is capable of inducing structural grey and white matter changes in PFC and SMA regions 11,43,50,51 , we further hypothesized it to potentially lead to cognitive transfer effects.…”
Section: Discussionmentioning
confidence: 99%
“…Although the neurophysiological effects of a single tDCS session are shown to last a few minutes to a couple of hours after the end of stimulation 30,31 , it is nevertheless capable of inducing long-term structural plasticity in the form of rearranged synaptic networks and spinogenesis as established through animal models 32,33 . Similarly, in older adults, training combined with tDCS spread over multiple days was shown to modulate functional connectivity and microstructural brain alterations associated with cognitive performance gains 34 . In line with these ndings, prefrontal tDCS applied during motor practice may therefore in uence the balance learninginduced prefrontal neural changes that support ongoing balance performance; also affecting the transfer to cognitive tasks assessed after a time delay that outlasts the acute neurophysiological effects of tDCS.…”
Section: Introductionmentioning
confidence: 97%